Kinematics Analysis of a Planar Symmetric (CRR)2S-(3R)2R Parallel Mechanism - Jie Li; Linxian Che; Li Du; Xin Zheng (Jixie chuandong)
Taking a planar symmetrical (CRR)2S-(3R)2R parallel mechanism with two translations and two rotations (2T2R) as the research object，based on the position and orientation characteristic set theory analyzes the number and nature of the mechanism’s degree of freedom and then this study analyzes its kinematics problems. The coordinate transformation method is applied to establish a set of nonlinear equations for the positive solution of the mechanism position，and the differential evolution algorithm is used to find the set of equations. The analytical expressions for the inverse solution of the mechanism are derived，and numerical examples are used to verify the correctness of the forward and inverse solutions of the mechanism. The vector method is used to derive the velocity and acceleration expressions of the mechanism，and Matlab is applied to program the position，velocity and acceleration curves of the mechanism. At the same time，Adams is used for kinematics simulation，and the maximum error between the Matlab theoretical curve and the Adams simulation curve is obtained. The result shows that the kinematic analysis curves of the two are basically the same，indicating that the theoretical analysis of the mechanism is correct and reliable.